2016
DOI: 10.1177/2047487316651825
|View full text |Cite
|
Sign up to set email alerts
|

Occult coronary artery disease in middle-aged sportsmen with a low cardiovascular risk score: The Measuring Athlete’s Risk of Cardiovascular Events (MARC) study

Abstract: Coronary CT detects occult CAD in almost one in five asymptomatic sportsmen aged ≥45 years after a normal SME that included resting and bicycle exercise ECG. CACS reveals most of the relevant CAD with limited additional value of contrast-enhanced CCTA. The NNS in order to prevent one cardiovascular event compares favourably to that of other screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 44 publications
1
67
3
3
Order By: Relevance
“…The number of male athletes with a CAC=0 in this study was significantly higher than in a previous study from Germany of 108 middle-age marathon runners of similar age but higher risk profile 8 and slightly higher than a Dutch study of 318 asymptomatic athletic men with a generally low risk profile where 37% were former or current smokers. 10 The percentage of male athletes with a CAC >100 Agatston units was also lower in our study compared with the German marathon runners (18.9% versus 36.1%). 8 These observations suggest that the higher coronary calcium scores in previous studies likely reflected a higher atherosclerotic risk profile rather than a potentially deleterious exercise effect.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…The number of male athletes with a CAC=0 in this study was significantly higher than in a previous study from Germany of 108 middle-age marathon runners of similar age but higher risk profile 8 and slightly higher than a Dutch study of 318 asymptomatic athletic men with a generally low risk profile where 37% were former or current smokers. 10 The percentage of male athletes with a CAC >100 Agatston units was also lower in our study compared with the German marathon runners (18.9% versus 36.1%). 8 These observations suggest that the higher coronary calcium scores in previous studies likely reflected a higher atherosclerotic risk profile rather than a potentially deleterious exercise effect.…”
Section: Discussioncontrasting
confidence: 48%
“…Ultra-endurance athletes have also been reported to have a greater vasodilatory capacity compared with sedentary individuals. 29 In contrast, 3 previous studies have shown a higher burden of atherosclerosis in endurance athletes compared with controls, [8][9][10] raising concerns that prodigious amounts of exercise may actually accelerate the coronary atherosclerotic process. These studies included athletes with established risk factors for CAD or could not exclude the possibility that many of them had adopted an active lifestyle in middle age and had higher risk factors during most of their lives.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…CACS and CTCA have proven predictive value for MI and SCD over clinical risk stratification 83 84. In a recent study of 318 asymptomatic male athletes aged over 45 years, CT identified occult CAD in 19%, where exercise ECG testing was negative during a high work load 85. Other studies suggest that CACS improves prediction of MI or death due to CAD only in intermediate-risk patients (Framingham Risk Score 10%–20%)86 but adds no predictive power for those with low risk (Framingham Risk Score <10%) as assessed by traditional cardiovascular disease risk factors 86–88.…”
Section: Future Directions In the Management Of Mature Athletesmentioning
confidence: 99%